SYSTEM ANALYSIS OF THE LEVEL OF TRAINING OF POSTGRADUATE EDUCATION OF SECONDARY MEDICAL PERSONNEL (World Bulletin of Public Health, 2024)
New medical technologies and modern development of medical science, which determine the need for systematic postgraduate training, are considered. So far, there is no scientifically grounded technology for the implementation of continuing medical education and the motivation of nursing staff to systematic advanced training has not been studied. The article presents the opinion of experts regarding independent education in specialty of middle medical personnel and analysis of motivation to systematic advanced training